2010
DOI: 10.2355/isijinternational.50.561
|View full text |Cite
|
Sign up to set email alerts
|

Coating Degradation in Hot Press Forming

Abstract: The thermo-mechanically induced microstructure changes occurring in a type 1 aluminized coating on hot press forming (HPF) steel were studied in detail. The formation of intermetallic phases at the soaking temperature prior to die quenching revealed that the coating matrix consists mainly of FeAl 2 intermetallic phase by the time the press forming carried out. Kirkendall void formation was observed to take place. The thermal oxidation of aluminized coating during HPF was found to be limited, with the coating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 11 publications
(9 reference statements)
5
81
0
1
Order By: Relevance
“…The first layer has been identified as Fe 2 Al 5 in the work of Grigorieva and Drillet and co‐workers,15 Suehiro et al,16 and Im et al 18 Fan et al,19 however, identified it as a FeAl 2 layer resulting from the transformation of Fe 2 Al 5 due to the gradually increasing Fe content in the coating. The second layer has been identified as τ 1 Fe 2 SiAl 2 .…”
Section: Aluminized Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…The first layer has been identified as Fe 2 Al 5 in the work of Grigorieva and Drillet and co‐workers,15 Suehiro et al,16 and Im et al 18 Fan et al,19 however, identified it as a FeAl 2 layer resulting from the transformation of Fe 2 Al 5 due to the gradually increasing Fe content in the coating. The second layer has been identified as τ 1 Fe 2 SiAl 2 .…”
Section: Aluminized Coatingmentioning
confidence: 99%
“…The high temperature behavior of type 1 aluminized coating on hot stamped steel was studied by Drillet,11Grigorieva et al,15 Takagi et al,12 Suehiro et al,16 Maki et al,17 Im et al,18 Fan et al,19 Jenner et al,20 and Borsetto et al21…”
Section: Aluminized Coatingmentioning
confidence: 99%
“…These voids are due to a mass imbalance caused by the large difference in the diffusivity of Fe and Al. [7,14] This microstructure is similar to that of Al-10 pct Si coatings heat treated using a conventional furnace heating. [15,16] The difference in microstructure between direct resistance Joule heating and furnace heating is the absence of the Si-containing layer in the case of direct resistance Joule heating.…”
Section: Methodsmentioning
confidence: 90%
“…Different coatings have been tested to satisfy these requirements such as Al-alloy coatings, Zn, and Zn alloy coatings. [7,8] Zn-based coatings can in principle provide cathodic protection to PHS. Zn and Zn alloy coatings make the PHS susceptible to liquid metal embrittlement (LME) due to the low melting temperature of Zn and the formation of Zn-Fe intermetallic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The coating does however not provide cathodic protection, and the corrosion of the underlying steel can occur in areas where the coating layer has been damaged during the diequenching. 15,16) Zn and Zn-alloy coatings have been developed to address this issue, as Zn and Zn-alloys have the advantage of providing cathodic protection to steel. The use of a Zn coating results in a mild form of liquid metal induced embrittlement (LMIE), characterized by microcrack formation and the presence of a thick ZnO layer at the surface after die-quenching.…”
Section: Introductionmentioning
confidence: 99%